2014
DOI: 10.1111/etho.12064
|View full text |Cite
|
Sign up to set email alerts
|

Asserting Existence: Agentive Narratives Arising From the Restraints of Seeking Asylum in East Anglia, Britain

Abstract: This article is based on fieldwork (2002–2003) in Great Yarmouth and Norwich in Britain with asylum seekers from Iraq, Iran, Kenya, Kosovo, Congo, and Montenegro as they await the outcome to their application for refugee status. During this period of liminality, their narratives were both urgent and repetitive expressions of their current immigration status and, to a lesser extent, their past experiences. In this article, I consider how such narratives are elicited by asylum seekers to craft an agentive capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…The usefulness of liminality has been noted by other authors who identify it as a pivotal concept in relation to situation-specific theory of well-being in refugee women experiencing transition. 20 The liminal aspect of this reality describes an "in-between" space in which change and adaptation occur. Because this study involves women from different ethnic, religious, and racial geographical origins, liminality denotes a "transcultural space in which strategies for personal and communal selfhood is elaborated."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of liminality has been noted by other authors who identify it as a pivotal concept in relation to situation-specific theory of well-being in refugee women experiencing transition. 20 The liminal aspect of this reality describes an "in-between" space in which change and adaptation occur. Because this study involves women from different ethnic, religious, and racial geographical origins, liminality denotes a "transcultural space in which strategies for personal and communal selfhood is elaborated."…”
Section: Discussionmentioning
confidence: 99%
“…She saw her pregnancy in Canada as an opportunity to regain a sense of connection that had been previously lost. She offered the following explanation during her interview: [19][20] Tulun articulated the loss imposed on her by HIV infection and the cultural expectations surrounding motherhood in her country of origin. She articulated that "'here," in Canada, women living with HIV infection have an opportunity to reconnect by fulfilling these expectations.…”
Section: Feeling Disconnected From Culturementioning
confidence: 99%
“…Hassan's case illustrates the ways in which asylum seekers can oscillate between “stagnation and immobility” and “the agentive action of struggle, persistence, and communication” (Rainbird , 464). Tension between possibility and foreclosure, between desire and defeat, was a constant in asylum seekers’ lives.…”
Section: Between Possibility and Foreclosurementioning
confidence: 99%
“…Moreover, some asylum seekers suggested that the pain associated with the political asylum process could inflict enduring psychic distress. As Joseph told me, “Even if they [asylum seekers] are granted, they've gone through some kind of psychological torture.” Waiting itself could thus be experienced as a kind of “psychological imprisonment” whose effects outlasted the determination of the asylum claim (Rainbird , 470).…”
Section: Lived Consequences Of “Existential Limbo”mentioning
confidence: 99%
See 1 more Smart Citation